2023
DOI: 10.3390/nu15122641
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides Extracted from Dendrobium officinale Grown in Different Environments Elicit Varying Health Benefits in Caenorhabditis elegans

Abstract: Dendrobium officinale is one of the most widely used medicinal herbs, especially in Asia. In recent times, the polysaccharide content of D. officinale has garnered attention due to the numerous reports of its medicinal properties, such as anticancer, antioxidant, anti-diabetic, hepatoprotective, neuroprotective, and anti-aging activities. However, few reports of its anti-aging potential are available. Due to high demand, the wild D. officinale is scarce; hence, alternative cultivation methods are being employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In the search for effective treatments for MASLD, Dendrobium nobile, a traditional Chinese medicinal herb, has gained attention due to its diverse pharmacological effects [ 5 ]. Containing a variety of bioactive components such as polysaccharides, alkaloids, and polyphenolic compounds, it has been proven to improve metabolic disorders, reduce fat accumulation, lower inflammation levels, and improve insulin resistance, thereby holding potential value in the treatment of MASLD [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for effective treatments for MASLD, Dendrobium nobile, a traditional Chinese medicinal herb, has gained attention due to its diverse pharmacological effects [ 5 ]. Containing a variety of bioactive components such as polysaccharides, alkaloids, and polyphenolic compounds, it has been proven to improve metabolic disorders, reduce fat accumulation, lower inflammation levels, and improve insulin resistance, thereby holding potential value in the treatment of MASLD [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…5) Modern pharmacological studies have shown that D. officinale has health-promoting functions, such as enhancing immunity, 6,7) inhibiting tumors, 8,9) lowering blood sugar, 10) anti-oxidizing, 11) and delaying aging. 12) In view of its health benefits, D. officinale has been added to various beverages, functional liquids, capsules, and powders.…”
Section: Introductionmentioning
confidence: 99%